Interactivity of Satellite Channels’ Websites and Their Role in Covering the Russian-Ukrainian War - Salman, Ali Khalaf; Fadhil, Ali Abbas (ALBAHITH ALALAMI, 2025)
This research aims to analyze media performance and examine the interactivity of the websites of the Al-Sharqiya and Al-Hadath channels—as well as their corresponding Facebook pages—in order to understand the interactions between these platforms and their target audiences during the conflict between Russia and Ukraine. The study further discusses the significance of these websites in disseminating news and events during times of war and crisis and evaluates their capacity to provide accurate, up-to-date information to the intended audience. Classified as descriptive research, the researcher employed a survey method combined with content analysis tool for a sample collected using an exhaustive sampling method. A comprehensive sample was gathered—totaling 276 topics—during a single programming cycle from February 24, 2022, to May 24, 2022. The findings revealed a notable convergence between the two websites concerning topics related to the ongoing Russia-Ukraine conflict, with military and political subjects ranking first and second, respectively. Moreover, both platforms exhibited similar patterns in user engagement, with the “Like” function emerging as the predominant mode of interaction. In addition, regarding the sources of information presentation, the category “Live Broadcast from the Al-Arabia Al-Hadath Website” ranked highest.